Superconducting gap and pair breaking in CeRu2 studied by point contacts - Moskalenko, A. V.; Naidyuk, Yu. G.; Yanson, I. K.; Hedo, M.; Inada, Y.; Unicode`>Ōnuki, Y. <font face=`Lucida Sans; Haga, Y.; Yamamoto, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The superconducting gap in a CeRu2 single crystal is investigated by point contacts. BCS-like behavior of the gap D in the temperature range below Tc* (Tc * < Tc, where Tc is the critical temperature) is established, indicating the presence of a gapless superconductivity region (between Tc* and Tc). The pair-breaking effect of paramagnetic impurities, supposedly Ce ions, is taken into consideration using the Scalski-Betbeder-Matibet-Weiss approach based on Abrikosov-Gorkov theory. It allows us to recalculate the superconducting order parameter Da (in the presence of paramagnetic impurities) and the gap Dp (in the pure case) for the single crystal and for the previously studied polycrystalline CeRu2. The value 2Dp(0)»2 meV, with 2Dp(0)/kBTc»3.75, is found in both cases, indicating that CeRu2 is a "moderate" strong-coupling superconductor.